Parish clergy in the diocese of León in the 18th century - Pérez Álvarez, María José (Cuadernos de Historia Moderna, 2021)
The Concordat of 1851 marked the beginning of substantial restructuring of the diocesan territory of León, which was not completed until a few decades later. As a result, new archpriestships emerged while others were annulled, and some parishes changed their boundaries. Apart from these territorial changes, another question that was of particular interest to the prelates was the spiritual and moral health of the diocesan province under their authority. One of the means to gather information on this was through pastoral visits. Based on such visits conducted in the mid-18th century, “secret instructions” were drawn up for the vicars, who were charged with correcting the clergy’s behaviour, which had revealed itself to be reprehensible.
Keywords: Early Modern Period; Diocese; León; pastoral visits; ecclesiastics; parish priests